(untitled)
The irrational number \(Φ = 1+5 2\) or \(φ =âˆ’1+5 2\) is well known as golden ratio.The binet forms \(L_n = Φ^n + (âˆ’φ)^n\) and \(F_n = Φ^nâˆ’(âˆ’φ)^np5 \) define the well known Lucas and Fibonacci numbers. In the present paper, we generalize the binet forms \(Φ_n(x,y) = 1y· 5 [(x + yΦ)^nâˆ’(xâˆ’yφ)^n]\) and \(π_n(x,y)=[(x + yΦ)^n +(xâˆ’yφ)^n]\). As a result we obtain a pair of two variable polynomial which are new combinatorial entities. Many convolution identities of Ln and Fn are getting added to the recent literature. A generalized convolution identities will be a worthy enrichment of such combinatorial identities to the current literature., number=1-2, journal=Journal of Informatics and Mathematical Sciences, year=2018, month=Aug., pages=227–236